2012
DOI: 10.4236/ojas.2012.24033
|View full text |Cite
|
Sign up to set email alerts
|

An initial investigation replacing fish meal with a commercial fermented soybean meal product in the diets of juvenile rainbow trout

Abstract: The inclusion of PepSoyGen (PSG), a commercially-available fermented soybean meal product, was evaluated with juvenile rainbow trout, Oncorhynchus mykiss in an initial 70-day feeding trial, with a supplemental trial involving a subset of the experimental diets continuing for an additional 40 d. Six diets containing 0%, 10%, 20%, 30%, 40%, or 50% PSG, with the PSG directly replacing fish meal, were used in the first trial. There were no significant differences in weight gain or feed conversion ratio between the… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

4
37
2

Year Published

2014
2014
2024
2024

Publication Types

Select...
5
1

Relationship

1
5

Authors

Journals

citations
Cited by 36 publications
(43 citation statements)
references
References 55 publications
4
37
2
Order By: Relevance
“…Although the feed conversion ratios and HSI values in this study were higher than those reported in other rainbow trout feeding trials (Adelizi et al 1998;Cheng et al 2003a, b;Barrows et al 2008b), including those evaluating fermented soybean meal (Barnes et al 2012, the differences in study durations, fish sizes, and feeding levels make any comparisons among these studies problematic. The significantly elevated hepatosomatic index in the McConaughy strain may indicate increased fat deposition due to the slower growth rate and decreased feed efficiency than that observed with the Shasta strain (Takeuchi and Watanabe 1982).…”
Section: Discussionmentioning
confidence: 50%
See 3 more Smart Citations
“…Although the feed conversion ratios and HSI values in this study were higher than those reported in other rainbow trout feeding trials (Adelizi et al 1998;Cheng et al 2003a, b;Barrows et al 2008b), including those evaluating fermented soybean meal (Barnes et al 2012, the differences in study durations, fish sizes, and feeding levels make any comparisons among these studies problematic. The significantly elevated hepatosomatic index in the McConaughy strain may indicate increased fat deposition due to the slower growth rate and decreased feed efficiency than that observed with the Shasta strain (Takeuchi and Watanabe 1982).…”
Section: Discussionmentioning
confidence: 50%
“…Within each strain, the diet containing 15 % fish meal and 35 % fermented soybean meal produced similar growth results to the diet containing 40 % fish meal and no fermented soybean meal. This diet contains an increase in the amount of fermented soybean meal and a decrease in the amount of fish meal from the diet successfully used by Barnes et al (2012) during a feed trial with McConaughy strain rainbow trout. Using different fermentation techniques and substantial amino acid supplementation, Yamamoto et al (2010) were able to completely eliminate the fish meal in rainbow trout diets containing 47.6 % fermented soybean meal.…”
Section: Discussionmentioning
confidence: 98%
See 2 more Smart Citations
“…Barnes et al (2013) also reported that A. oryzae-B. subtilis-fermented soybean meal could be used to replace a moderate amount of dietary fish meal in feeds for Rainbow Trout Oncorhynchus mykiss, albeit with reduced growth performance and elevated food conversion ratio (FCR; Barnes et al 2012Barnes et al , 2013. These studies suggest fermentation may be equally or more effective than other, more costly processing strategies attempting to improve the acceptance and utilization of soy protein products in feeds for carnivorous fish.…”
mentioning
confidence: 91%